Comparative analysis of promising current sources for electrical impedance tomography in an extended frequency range (Visnyk NTUU KPI Seriia - Radiotekhnika Radioaparatobuduvannia, 2012)
Iintroduction: Features of biological impedance meters are listed and requirements for their current sources are formed. Formulation of the problem: A review of existing current sources and puts forward proposals to explore the parameters of some of them and the current source on a fully integrated differential amplifier with active feedback. Methods of research and analysis of the results: Describes the method of measuring the parameters of current sources, critically reviewed the results and recommendations for the use of these sources. Conclusion: The accomplishments and weaknesses of the investigated sources, given ways to improve their parameters are considered.